2005
DOI: 10.1002/glia.20279
|View full text |Cite
|
Sign up to set email alerts
|

His36Pro point‐mutated proteolipid protein retained in the endoplasmic reticulum of oligodendrocytes in the Shaking pup

Abstract: The shaking pup (shp) is a canine mutation that affects the myelin protein proteolipid protein (PLP) and its smaller and less abundant isoform, DM20, with proline replacing histidine(36), resulting in a severe myelin deficiency in the central nervous system. We present evidence that the mutation leads to disrupted trafficking of the shp PLP/DM20 within oligodendrocytes. Immunohistochemical studies revealed significantly reduced levels of PLP/DM20 and other major myelin components such as myelin basic protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(61 reference statements)
0
3
0
2
Order By: Relevance
“…Thus different structural isoforms of the proteins may exist which in this manner might thus dictate their distinct lateral membrane localization, which in turn determines the protein's fate, in terms of recruitment in distinct vesicles and ensuing transport. In this context, it has been shown that in the PLP gene mutant shp (shaking pup) the mutated PLP selectively accumulates in the rough ER, i.e., its trafficking is perturbed [69], as has been reported to occur for many other mutations in PLP [51,70]. The shp mutation involves a substitution of the conserved amino acid His by Pro (an alpha helix breaker) in the first extracellular loop (Fig.…”
Section: Membrane Microdomains In Olg: Role Of Galcer Sulfatide and mentioning
confidence: 92%
“…Thus different structural isoforms of the proteins may exist which in this manner might thus dictate their distinct lateral membrane localization, which in turn determines the protein's fate, in terms of recruitment in distinct vesicles and ensuing transport. In this context, it has been shown that in the PLP gene mutant shp (shaking pup) the mutated PLP selectively accumulates in the rough ER, i.e., its trafficking is perturbed [69], as has been reported to occur for many other mutations in PLP [51,70]. The shp mutation involves a substitution of the conserved amino acid His by Pro (an alpha helix breaker) in the first extracellular loop (Fig.…”
Section: Membrane Microdomains In Olg: Role Of Galcer Sulfatide and mentioning
confidence: 92%
“…Gow et al [9] have proposed that mutated PLPs are not transported to the cell surface of oligodendrocytes as a result of misfolding, and that this invokes an unfolded protein response in the cell that may or may not result in death [10]. We have shown, however, that cells with very distended RER are capable of making and maintaining myelin sheaths in the shp [7,11]. The point mutation in this model results in a proline-for-histidine substitution in the second exon of the PLP gene, which likely results in a highly misfolded protein [12].…”
mentioning
confidence: 71%
“…First, disruption of PLP production results in a failure of development of the intraperiod line of myelin sheaths around some axons, yet a multilamellar sheath that is MBP + /PLP À can be formed [6]. Second, in two mutants, the md rat and shp, rough endoplasmic reticulum (RER) in oligodendrocytes is markedly distended, likely resulting from the accumulation of the mutated PLP [7].…”
mentioning
confidence: 99%
“…Zusammenhang der Erkrankung mit einer Mutation im PLP-Gen als wahrscheinlich angesehen (Yanagisawa et al 1987;Nadon et al 1990). Blockade in der Oligodendrozytenentwicklung (Duncan et al 1983;Inuzuka et al 1986;Yanagisawa et al 1987;Song et al 2006). Einzelheiten über den Mechanismus dieser Blockade sind nicht bekannt.…”
Section: Syndroms Und Der Abnormalen Expression Von Plp Und Dm-20 Wir...unclassified
“…Der Aminosäurenaustausch von Histidin zu Prolin ist in der ersten Transmembrandomäne des Proteins lokalisiert (Nadon et al 1990). Da andere Oligodendrozyten sich normal entwickeln, konnte bisher noch nicht geklärt werden (Song et al 2006).…”
Section: Syndroms Und Der Abnormalen Expression Von Plp Und Dm-20 Wir...unclassified